Emergency percutaneous coronary intervention for left main trunk thrombus following orthotopic heart transplantation - Tsuji, Masaki (ESC Heart Fail, 2019)
Heart transplantation (HTx) is the gold standard therapy to improve quality and quantity of life in end‐stage heart failure patients. However, recipients are at risk of experiencing allograft rejection and post‐transplant complications, in the acute as well as chronic phase. A 43‐year‐old man with a history of left ventricular non‐compaction underwent orthotopic HTx. On Day 7, transthoracic echocardiography showed a sudden decrease in cardiac function with hypokinesis in a left ventricular anterior wall distribution. Coronary angiography revealed a large thrombus in the left main trunk. With intra‐aortic balloon pump support, emergency percutaneous coronary intervention was performed. Endomyocardial biopsy showed no rejection. A left main trunk thrombus is rare in the early phase after HTx, but it can be a life‐threatening complication. Transthoracic echocardiography is well known to be important in the management of heart transplant recipients, and coronary angiography as well as myocardial biopsy should be considered when left ventricular wall motion is impaired.